Cross-coupling reactions of nucleoside triphosphates followed by polymerase incorporation. Construction and applications of base-functionalized nucleic acids - Hocek, Michal; Fojta, Miroslav (Organic & biomolecular chemistry, 2008)
Construction of functionalized nucleic acids (DNA or RNA) via polymerase incorporation of modified nucleoside triphosphates is reviewed and selected applications of the modified nucleic acids are highlighted. The classical multistep approach for the synthesis of modified NTPs by triphosphorylation of modified nucleosides is compared to the novel approach consisting of direct aqueous cross-coupling reactions of unprotected halogenated nucleoside triphosphates. The combination of cross-coupling of NTPs with polymerase incorporation gives an efficient and straightforward two-step synthesis of modified nucleic acids. Primer extension using biotinylated templates followed by separation using streptavidine-coated magnetic beads and DNA duplex denaturation is used for preparation of modified single stranded oligonucleotides. Examples of using this approach for electrochemical DNA labelling and bioanalytical applications are given.
Keywords: DNA řízené RNA-polymerasy; DNA-Directed DNA Polymerase; Nucleic Acids; Base Sequence; Nucleotides; DNA-dependentní DNA-polymerasy; nukleové kyseliny; polyfosfáty; DNA-Directed RNA Polymerases; nukleotidy; Polyphosphates; sekvence nukleotidů